Review of agricultural production systems in eastern Africa in relation to food and nutrition security and climate change - Hunt, Sarah; Eshete, Getachew; Tadesse, Million; Eshetu, Zewdu (2019)
The goal of this paper is to provide a unified resource for Eritrea, Djibouti, Somaliland, Somalia, Ethiopia, Kenya, Uganda, Rwanda and Tanzania. For each country the review covers the topics of livestock production systems and agroecological zones, food and nutrition security, climate change, greenhouse gas (GHG) emissions and climate-smart agriculture (CSA) with a focus on the role of, or impact on, livestock systems. Each of these topics is broad and many excellent studies and reviews have been produced covering these topics either at the country level or for the entire East Africa region. It is the goal of this paper to provide an accessible introduction to these topics and to direct readers to the resources that exist for gathering detailed information on livestock production, food nutrition and security, climate change, GHG emissions and climate-smart livestock production in each country.